Dietary Behaviors and Biochemical Serum Indicators in Adults with Type 2 Diabetes Mellitus from a Rural Region of Jalisco, Mexico - Monica NAVARRO-MEZA; Karina Anai GARCIA-CAMACHO; Felipe SANTOYO-TELLES; Antonio LÓPEZ-ESPINOZA; Omar ARROYO-HELGUERA (Tehran University of Medical Sciences, 2018)
No Abstract###